Producing online news digital skills, stronger stories - Thornburg, Ryan (CQ Press, 2011)
"The dazzling speed of change in online journalism can mask a simple truth: online news is still news. Cutting-edge technology benefits the audience only when journalists apply it in the service of good stories. Building on a foundation of news stories, Producing Online News shows students how to use the right tools to get the right information to the right people at the right time. The goal is to become a full-fledged online news producer and transform stories into a complete news experience for an ever more demanding audience